Longitudinal monitoring of patient limb loading throughout ankle fracture rehabilitation using an insole load monitoring system: a case series. Issue 2 (March 2017) - North, Kylee; Kubiak, Erik N.; Rothberg, David L.; Lajevardi-Khosh, Arad; Petelenz, Tomasz J.; Hitchcock, Robert W.; Stuart, Ami R.
Abstract : Background: The purpose of this prospective, direct observational study was to evaluate limb loading in lower extremity orthopaedic trauma patients using a novel insole sensor, the Ambulatory Tibial Load Analysis System (ATLAS). Methods: Three patients from a level I trauma center, one with a trimalleolar ankle fracture, one with a distal, spiral fracture of the tibia and fibula at the same level, and one with a bimalleolar ankle fracture were observed using an insole load monitoring system to record their weight bearing during standard of care rehabilitation. No clinical decisions were made based on the limb loading data. The primary study measures were limb-loading data provided by the ATLAS and patient reported physical function as measured by the PROMIS Physical Function Computer Adapted Test. Results: The ATLAS provided 8-12 wk of continuous limb loading data, with raw loading data, duration of insole sensor and CAM walker wear, daily step count, median load per day, and periods of static and dynamic loading for three patients with varying ankle fractures. Conclusions: The findings of this case study support the use of the ATLAS sensor in evaluation of limb loading in patients with lower extremity fracture. The data suggest that the current weight bearing prescription may not be sufficient for all patients and that personalized protocols are warranted.